KUALITAS KINERJA PERUSAHAAN DAERAH (BUMD): ANALISIS BEHAVIORAL INTENTIONS PELANGGAN PADA PERUSAHAAN DAERAH AIR MINUM KOTA SURABAYA - Sukesi Sukesi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
Drinking water District Company (PDAM) as a public service company must create professional service. The availability of fresh and healthy water is an important need for the dweller of Surabaya city because the pure water pollution remains in high degree, and the source of PDAM’s water fountain is limited. PDAM as a service company that serves the society need and concerns with the basic need of human being that has not been substituted yet. For that reason, PDAM is required to give professional services continuously. PDAM as the only one public company that has the highest customer list in the matter of complaining as written in mass media. So that, it needs evaluation and innovation forward the PDAM quality service.This research is done by survey in the form of questionnaire to the PDAM customer of Surabaya. Research sampling are 488 customers that consist of three groups of customer based on their experience of getting problem They are the group of uncomplicated customer, of complicated but can be solved customer, and of complicated and can not be solved customer.Using the technique of factor analysis, regression analysis, and chi-square simultaneously the quality of service influence toward the intention which is taken (behavioral intentions) for the complicated and can not be solved customer either simultaneously or partially the service quality that has not influenced toward the behavioral intentions of the PDAM customer of Surabaya.